ALANINE AMINOTRANSFERASE ACTIVITY IN RATS OF DIFFERENT AND IN CONDITIONS OF PERIODICAL INJECTION OF MULTIPROBIOTIC «SYMBITER® ACIDOPHILIC» - Torgalo L.О.; Таburets О.V.; Beregova, T.V.; Ostapchenko, L.I.; Yankovsky, D.S. (World of Medicine and Biology, 2012)
It was established, that activity of alanine aminotransferase in serum is decreasing in rats with age (from 3 to 18 months). Periodical administration (every 3 months during 10 days) to the rats multiprobiotic "Symbiter® acidophilic" prevents the age-related changes in the enzyme activity. Thus activity of alaninaminotranspherase may be serve as biomarker of aging and periodical use of multiprobiotic may to some extent prevent age-related changes in activity of alanine aminotransferase.